(untitled) (Palimpsesto, 2025)
This essay discusses the contemporary relationship between mining and urbanization in northern Chile, emphasizing the limited conceptual renewal with which this subject is currently addressed. This lack of renewal can be seen in the prevalence of the ideas of company town and camp in historiographical and social-scientific studies on this relationship, thereby contributing to an isomorphic representation of the mining-urbanization relationship. Considering this, it is propose a "geographically extended" understanding of the mining-urbanization relationship in northern Chile, whose originality lies in understanding its articulation through the concepts of "transurbanization" and "transregionalization."